RELATIONSHIP BETWEEN KNOWLEDGE OF PREGNANT MOTHERS AND THE EVENT OF LOW BIRTH WEIGHT IN MUNA DISTRICT, SOUTH SULAWESI - Nur Fadhliah Gani (Pengurus Daerah Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI) Sulawesi Tenggara, 2022)
In Indonesia, Low Birth Weight (LBW) is the main cause of neonatal death. This study aims to determine the relationship between knowledge of pregnant women with low birth weight. This study was a cross-sectional on women who gave birth at the obstetrics and gynecology unit at the government-health service in Muna, Southeat Sulawesi. The sample size in this study was 108 people who were selected using a simple random sampling technique. The results of the study showed there was a relationship between knowledge of pregnant women and the incidence of low birth weight with P Value < 0.001 or p < = 0.05. Maternal knowledge about healthy preganancy, risk of LBW, and nutrition during pregnancy need to be considered in the prevention of LBW.